A Compressor - System Digital Twin for Performance Prediction Under a Wide Range of Flow and Operating Conditions - Alberto Serena; Lars E. Bakken (Chemical Engineering Transactions)
Turbomachines are essential equipment in propulsion, energy conversion and process engineering; their efficiency and optimization require the exploration of tailored designs and the exploitation of the full machine capability. The compressor behaviour in the overall system under design and off-design conditions needs to be adequately modelled and integrated. A blend of theory, laboratory experiments, operational experience, data analysis and process simulation have been employed for an accurate description of the machine behaviour. Testing benefits from a responsive rig, allowing modification of layout and key parameters. The model under study is vital in the definition of the actual surge margin and of a suitable recovery strategy; an early detection is needed to safeguard stable operation and avoid unnecessary stresses. The main focus is the validation of the system model at the boundary of the operating envelope, and, in particular, the study and prediction of the trip trajectory, caused by disturbances in the power input, or variations in inlet composition, or downstream equipment pressure build-up. The experimental campaigns, data processing and model validation are presented; a wide test matrix covers the parameters of specific interest for chemical and process engineering plants; sensitivity studies are performed on molar weight and mixture composition, exploring not only machine capabilities in terms of stability range and performance degradation, but also the software real gas models and the influence of real operating conditions and machine aerodynamic design.